Proximate Composition of Thai and Cambodian Ready-to-Eat Insects - Nils Th. Grabowski; Ty Chhay; Sath Keo; Rachakris Lertpatarakomol; J. Kajaysri; Kyung-Yun Kang; Phalla Miech; Madeleine Plötz; J. Mitchaothai (Journal of Food Quality, 2021)
Samples of ready-to-eat snacks based on Lethocerus indicus, Gymnogryllus vietnamensis, Tarbinskiellus portentosus, Teleogryllus mitratus, Bombyx mori, Omphisa fuscidentalis, and Cybister limbatus were purchased in Cambodia and Thailand, and their proximate chemical composition (including Na and Cl) was analysed. Comparing the results with the few existing references from the literature (based on unprocessed specimens), marked differences occurred. This was expected as the insect chemical composition varies strongly intra- and interspecifically due to taxon, feeding, instar, and processing, among others. In general, the insects mainly consisted of fat (35 to 60%) and protein (25 to 38%), with 2 to 16% nitrogen-free extract, 2 to 15% fibre, 3 to 5% ashes, 0.4 to 1.6% Na, and 0.6 to 1.4% Cl (dry matter base). In this way, this contribution adds to the compositional knowledge about traditional insect-based foodstuffs. The combination of high fat and protein with low carbohydrates makes them suitable to combat nutrition disorders.
Keywords: Insect Utilization and Effects; Animal and Plant Science Education; Neurobiology and Insect Physiology Research